Tungsten diselenide (WSe2) as a high capacity, low overpotential conversion electrode for sodium ion batteries. Issue 123 (24th November 2015) - Share, Keith; Lewis, John; Oakes, Landon; Carter, Rachel E.; Cohn, Adam P.; Pint, Cary L.
Abstract : Tungsten diselenide (WSe2 ) is demonstrated as an efficient electrode for sodium ion batteries for the first time. Abstract : Tungsten diselenide (WSe2 ) is demonstrated as an efficient electrode for sodium ion batteries for the first time. A high reversible capacity above 200 mA h g −1 is observed at 20 mA g −1 rate, with over 250 mA h g −1 capacity measured in the first sodium extraction. Assessment of electrolyte and binder materials on performance was examined and an EC/DEC electrolyte with CMC binder emerges to yield the highest capacity and cycling retention. Comparison between WS2 and WSe2 distinguishes WSe2 to exhibit superior performance due to more efficient energetics bearing a small overpotential <0.30 V. Ex situ analysis and imaging after cycling confirms a sodium-mediated conversion reaction that yields isolated domains of W metal or Na x Se and reformation of WSe2 upon sodium extraction, enabling insight into the chemical storage pathway. This work highlights the promise of WSe2 compared to other conversion-based transition metal dichalcogenides as a practical material for sodium ion batteries.